2006
DOI: 10.1016/j.imlet.2005.11.027
|View full text |Cite
|
Sign up to set email alerts
|

The SH2 domain-containing inositol 5-phosphatase SHIP1 is recruited to the intracytoplasmic domain of human FcγRIIB and is mandatory for negative regulation of B cell activation

Abstract: Murine FcgammaRIIB were demonstrated to recruit SH2 domain-containing inositol 5-phosphatases (SHIP1/2), when their ITIM is tyrosyl-phosphorylated upon co-aggregation with BCR, and SHIP1 to account for FcgammaRIIB-dependent negative regulation of murine B cell activation. Although human FcgammaRIIB share the same ITIM as murine FcgammaRIIB and similarly inhibit human B cell activation, which among the four known SH2 domain-containing (tyrosine or inositol) phosphatases is/are recruited by human FcgammaRIIB is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
35
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 48 publications
0
35
0
Order By: Relevance
“…SHIP controls the accumulation of PI3K products at the plasma membrane by converting PI(3,4,5)P 3 to phosphatidylinositol 3,4-bisphosphate (9,10). SHIP was found to mediate most of the inhibitory functions of FcgRIIB in B cells (11). Taken together, these findings established the paradigm that SHIP recruitment to the ITIM of FcgRIIB is a dominant mechanism controlling SHIP activity and thus B cell activation via the PI3K pathway.…”
mentioning
confidence: 70%
See 1 more Smart Citation
“…SHIP controls the accumulation of PI3K products at the plasma membrane by converting PI(3,4,5)P 3 to phosphatidylinositol 3,4-bisphosphate (9,10). SHIP was found to mediate most of the inhibitory functions of FcgRIIB in B cells (11). Taken together, these findings established the paradigm that SHIP recruitment to the ITIM of FcgRIIB is a dominant mechanism controlling SHIP activity and thus B cell activation via the PI3K pathway.…”
mentioning
confidence: 70%
“…Previous studies report that SHIP-mediated inhibition of PI(3,4,5)P 3 and Ca 2+ flux is most active when FcgRIIB is coligated with the BCR (11,21). SHIP is also more highly phosphorylated in its C terminus with FcgRIIB coligation (22).…”
Section: Fcgriib Engagement Does Not Significantly Impact Recruitmentmentioning
confidence: 98%
“…However, unexpectedly, this inhibitory effect is retained in DT40 cells in the combined absence of the SH2 domain-containing tyrosine phosphatases, SHP1 and SHP2, which have been shown to bind to G6b-B (9, 10). The inhibitory effect of G6b-B is also retained in the absence of the SH2 domain-containing inositol phosphatase, SHIP, which has been shown to inhibit B cell receptor signaling through association with the Fc␥RIIb ITIM (43,44). An alternative pathway of inhibition could be through recruitment of the SH2 domain-containing inhibitor of Src kinases, Csk, to the two ITIMs in G6b-B.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that loss of tolerance in lpr mice results from the down-regulation of the low-affinity IgG inhibitory receptor FcγRIIB (Fc γ receptor IIB), thereby rendering their B cells incapable of terminating stimulatory signals delivered by autoantigen-containing immune complexes (6-8). However, the mechanisms whereby lack of FcγRIIB engagement would lead to autoimmunity, and whether additional factors contribute to autoimmunity, are still unclear.The SH2 domain-containing inositol 5′-phosphatase 1 (SHIP-1) phosphatase acts downstream of inhibitory cell-surface receptors (9-12), including the FcγRIIB, which is essential in opposing B-cell activation signals in mice and humans (13,14). FcγRIIB inactivation has been implicated in the development of autoreactive GC B cells and plasma cells (15), as well as in the regulation of the persistence and longevity of bone marrow plasma cells (16).…”
mentioning
confidence: 99%
“…The SH2 domain-containing inositol 5′-phosphatase 1 (SHIP-1) phosphatase acts downstream of inhibitory cell-surface receptors (9)(10)(11)(12), including the FcγRIIB, which is essential in opposing B-cell activation signals in mice and humans (13,14). FcγRIIB inactivation has been implicated in the development of autoreactive GC B cells and plasma cells (15), as well as in the regulation of the persistence and longevity of bone marrow plasma cells (16).…”
mentioning
confidence: 99%